KERENTANAN KONSUMEN DAN PERILAKU PEMBELIAN PRODUK MAKANAN KEMASAN - Simanjuntak, Megawati; Utami, Fulan Sri; Johan, Irni Rahmayani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
The purpose of this study was to analyze the effect of consumer vulnerability on food packaging purchasing behavior. This study used cross sectional. The sample of this study was 80 households in Bogors’ rural and urban area, West Java Province who consume food packaging product. That households was choosen by simple random sampling. Data were analyzed by descriptive, and inferential using independent samples t-test, logistic regression, and multiple linear regression.The result showed there was significant differences of households’ purchasing behavior on food packaging product and consumer vulnerability in rural and urban area. Consumer vulnerability was influenced by geographical location, while purchasing behavior was influenced by family expenditure and consumer vulnerability. Based on the results, consumer education is needed on how the settlement of consumer problems and recognition as well as providing information on consumer protection agency.